From Concept to Creation: Reviewing the Design, Fabrication, and Application of 3D Printing Technology - Ram Narendra Pimpalkar; A.P. Deshmukh (International Journal of Solid State Innovations & Research, 2024)
Additive manufacturing, or three-dimensional (3D) printing, has become a ground-breaking technology that goes beyond conventional production methods. 3D printing is transforming a variety of industries, including healthcare, aerospace, fashion, and automotive. It achieves this by layering materials to create objects layer by layer with unmatched flexibility, precision, and customisation. This article explores how 3D printing can change the way we manufacture solid 3D objects, as well as its uses, advantages, and potential future developments His initial approach required heating photopolymers with UV light in order to get the melting and solidification result. If someone loses their leg, we will be able to print a replacement one layer by layer. In principle, that is possible. There are several companies that offer 3D services to clients. Your design will be posted on the internet within a few hours after its publication.
Keywords: 3D; FDM; Flexibility; Precision; STL; UV light